Etos Agama Kelompok Tani Pawuah Sapakek, Nagari Sungai Nanam, Kab. Solok, Sumatera Barat - Sari, Nurmala; Shalihin, Nurus; Fauzi, Muhammad (Indonesian Center for Religion and Society Studies (InTReSt), 2024)
The study aim to describe the Religious Ethos Transformed by the Pawuah Sapakek Farmer Group. The study is focused on three aspects: First, the working principles that form the spirit of the Pawuah Sapakek farmer group. Second, how the Pawuah Sapakek farmer group interprets their work. Third, how the farmer group institutionalizes these values. Data collection techniques include observation and interviews. The study results indicate that the Pawuah Sapakek farmer group possesses three ethos. Firstly, the ethical morality ethos, which involves the ethics practiced within the group with the application of group work principles. Secondly, the fitrah ethos, where the Pawuah Sapakek farmer group works to maintain a relationship with God, uphold dignity, and support their families as part of their natural disposition as humans. Thirdly, the institutional ethos, where the Pawuah Sapakek farmer group accepts, executes, and preserves its work principles through the absorption of values, evaluation, discussion, and application in the group's collective fields and cooperatives to preserve and maintain these values through established rules within the group.